Pulmonary balloon valvuloplasty in a pregnant woman with severe pulmonary stenosis - Yusuf Ziya Şener; Levent Şahiner; Metin Okşul; Ergün Barış Kaya; Kudret Aytemir (KARE Publishing, 2019)
Pulmonary valvular stenosis is a rare valvular disease; it accounts for 7% to 12% of all patients with congenital heart disease. Patients with mild or moderate pulmonary stenosis (PS) are usually asymptomatic and the stenosis is often detected incidentally with echocardiography performed for another reason. Severe PS typically presents with symptoms related to increased right ventricular pressure and right heart failure. Valvular heart diseases are associated with increased morbidity and mortality in pregnancy due to cardiovascular alterations that occur during the gestational period, such as increased extracellular volume, a faster heart rate, and decreased venous return due to compression of the vena cava inferior by the enlarged uterus. While mild or moderate PS can be well tolerated in pregnancy, severe PS can lead to maternal and fetal perinatal complications. Presently described is the case of a pregnant patient with severe PS who successfully underwent balloon valvuloplasty in the third trimester.